Effects of wind on reservoir mixing and stratification: a case study from Kansas - Baker, Averi (Kansas State University, 2024)
There is a growing concern of harmful algal blooms (HABs) in freshwater aquatic systems, including reservoirs throughout Kansas due to their toxicity and increased frequency. The impact of wind events on the stratification dynamics within reservoirs has been proven to greatly affect the surrounding environment, including mixing dynamics within reservoirs and conditions for HABs to form. This research study used the well-established General Lake Model (GLM), a one-dimensional hydrodynamic model, to analyze the effects of different wind scenarios on stratification and potential for harmful cyanobacteria blooms in Marion Reservoir. The GLM model was calibrated and verified using temperature profile data collected from Marion Reservoir in 2022 and 2023. Wind scenarios reflecting potential changes in wind speed during the algal bloom season were then applied in the model to examine the effects of wind on reservoir mixing dynamics. This research exemplifies the crucial impact of wind magnitude on stratification of lakes and reservoirs. These results further show the complex relationship between wind events and reservoir mixing.
Keywords: Harmful algal blooms; Wind; Stratification; General lake model; Reservoir mixing; Cyanobacteria